2022
DOI: 10.3389/fmicb.2022.998849
|View full text |Cite
|
Sign up to set email alerts
|

Torquetenovirus in pregnancy: Correlation with vaginal microbiome, metabolome and pro-inflammatory cytokines

Abstract: Torquetenovirus (TTV) is a negative sense, single-stranded DNA virus present in many body fluids of apparently healthy individuals. At present, it is considered a non-pathogenic endogenous virus. TTV can be detected in the vagina of pregnant women, its abundance being modulated with the extent of immune system activation. Until now, there is only scarce information regarding the association between TTV and the composition of the vaginal environment. Therefore, this study aimed to assess the presence of TTV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…TTV, a member of the family Anelloviridae and transmitted through droplets of saliva, is an ubiquitous virus that is found in many types of clinical specimens and is involved in many diseases, e.g., liver diseases, cancer, thalassemia, non-malaria fever, and respiratory illness [ 58 ]. Recently, TTV DNA-positive was commonly found in the vagina of healthy pregnancy women [ 59 ]. In addition, TTV was also detected in blood of healthy donors [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…TTV, a member of the family Anelloviridae and transmitted through droplets of saliva, is an ubiquitous virus that is found in many types of clinical specimens and is involved in many diseases, e.g., liver diseases, cancer, thalassemia, non-malaria fever, and respiratory illness [ 58 ]. Recently, TTV DNA-positive was commonly found in the vagina of healthy pregnancy women [ 59 ]. In addition, TTV was also detected in blood of healthy donors [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we observed that TTV was significantly more prevalent in subjects with CT/NG rectal infections compared to non-infected individuals. This aspect is not surprising if we consider that TTV has been recognized as a marker of immune system activation [11].…”
Section: Plos Onementioning
confidence: 96%
“…While there is limited knowledge about the bacterial profiles of the anorectal microbiome in the context of chlamydial/gonococcal or HR-HPV infection, no data is currently available about the interaction between the anorectal microbiota and Torquetenovirus (TTV), a singlestranded DNA virus present in many body fluids and considered, at present, a non-pathogenic endogenous virus [11].…”
Section: Introductionmentioning
confidence: 99%